"\\frac{\u2202}{\u2202y}(2xy^2 - 2y) - \\frac{\u2202}{\u2202x}(3x^2y - 4x) = (4xy - 2) - (6xy - 4) = -2xy + 2."
Since "\\frac{[\\frac{\u2202}{\u2202y}(2xy^2 - 2y) - \\frac{\u2202}{\u2202x}(3x^2y - 4x)] }{ (2xy^2 - 2y)}\n\n=\\frac{ -2(xy - 1)}{2y(xy - 1) }= \\frac{-1}{y}" , a function of y alone,
we know that "e^{\u222b (\\frac{1}{y}) dy} = y" is an integrating factor.
Multiply both sides of the DE by "y" :
"(2xy^3 - 2y^2) dx + (3x^2y^2 - 4xy) dy = 0."
Now, this is an exact DE, because
"\\frac{\u2202}{\u2202y}(2xy^3 - 2y^2) = 6xy^2 - 4y = \\frac{\u2202}{\u2202x}(3x^2y^2 - 4xy)."
Since
"\u222b (2xy^3 - 2y^2) dx = x^2 y^3 - 2xy^2 + f(y)\\\\\n\n\u222b (3x^2y^2 - 4xy) dy = x^2 y^3 - 2xy^2 + g(x),"
the general solution is "x^2 y^3 - 2xy^2 = C" .
Comments
Leave a comment